Correlation of Microclimate of West Java on Caffeine and Chlorogenic acid in Coffea canephora var. robusta - Suci Awaliyah; Sri Nanan B. Widiyanto; Rijanti R. Maulani; Asep Hidayat; Ujang Dinar Husyari; Tati Suryati Syamsudin; Erly Marwani (3BIO: Journal of Biological Science, Technology and Management, 2022)
Caffeine and chlorogenic acid (CGA) are two compounds that play a role in determining the quality of coffee. The amount of the two compounds may vary depending on the environment where they are grown. This study aimed to determine the correlation between the local microclimatic condition and the concentration of caffeine and CGA in green and roasted beans of Robusta coffee from six different cultivation areas in West Java, Indonesia (i.e., Ciamis, Tasikmalaya, Sumedang, Kuningan, Cianjur, and Bogor). Samples of green beans and roasted beans were extracted with 70% methanol for caffeine analysis and ethyl acetate for CGA analysis. Caffeine and CGA were analyzed by UV-HPLC using a C18 shimpack gist shimadzu column, with an isocratic elution of methanol:water (1:1) at a 1 mL/min flow rate. Detection was performed at  λ272 nm and λ324 nm for caffeine and chlorogenic acid, respectively. Principal component analysis (PCA) was used to evaluate the correlation between microclimate with caffeine and chlorogenic acid. Results indicated that the concentration of caffeine ranged from 7.67 to 16.52% and 10.79 to 15.56% in the green and roasted bean coffee, respectively. The concentration of CGA ranged from 0.74 to 3.03% and 0.25 to 0.77% in the green and roasted bean coffee, respectively. Based on PCA analysis, the most influential microclimate on the caffeine concentration were the humidity, temperature, and altitude, with the total variance of PC1 and PC2 of  76.3%. However, there was no positive correlation between the measured microclimate and the CGA concentration. In conclusion, Robusta coffee's caffeine content is positively affected by the microclimatic condition (i.e., humidity, temperature, and altitude).